2020
DOI: 10.1111/pbi.13325
|View full text |Cite
|
Sign up to set email alerts
|

DcMYB113, a root‐specific R2R3‐MYB, conditions anthocyanin biosynthesis and modification in carrot

Abstract: Summary Purple carrots, the original domesticated carrots, accumulate highly glycosylated and acylated anthocyanins in root and/or petiole. Previously, a quantitative trait locus (QTL) for root‐specific anthocyanin pigmentation was genetically mapped to chromosome 3 of carrot. In this study, an R2R3‐MYB gene, namely DcMYB113, was identified within this QTL region. DcMYB113 expressed in the root of ‘Purple haze’, a carrot cultivar with purple root and nonpurple petiole, but not in the roots of two carrot cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 51 publications
3
98
0
Order By: Relevance
“…Recent studies of purple head Chinese cabbage revealed that total anthocyanin content is associated with high expression of only BrMYB2 (Bra004162) among these three BrMYBs, accompanied by upregulation of BrTT8 and a series of ABGs, including BrF3'H, BrDFR, BrANS, BrUGTs, and BrGSTs 10,27 . Recent advances have shown that MYBs activate bHLHs and ABGs through strong interactions with bHLHs to promote anthocyanin biosynthesis in crop plants [38][39][40] . In purple cauliflower and red cabbage, BoMYB2 is responsible for the purple trait by interacting with BoHLHs and related ABGs [15][16][17] , and homologous comparisons showed that BrMYB2 is highly homologous with BoMYB2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of purple head Chinese cabbage revealed that total anthocyanin content is associated with high expression of only BrMYB2 (Bra004162) among these three BrMYBs, accompanied by upregulation of BrTT8 and a series of ABGs, including BrF3'H, BrDFR, BrANS, BrUGTs, and BrGSTs 10,27 . Recent advances have shown that MYBs activate bHLHs and ABGs through strong interactions with bHLHs to promote anthocyanin biosynthesis in crop plants [38][39][40] . In purple cauliflower and red cabbage, BoMYB2 is responsible for the purple trait by interacting with BoHLHs and related ABGs [15][16][17] , and homologous comparisons showed that BrMYB2 is highly homologous with BoMYB2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the known genes of the pathway and their main regulators were differentially expressed between the two genotypes (Supplementary Table S4). Several genes were induced in purple tissues and they mainly comprised genes representing: i) the early step in the flavonoid/anthocyanin pathway, like chalcone synthase ( DcCHS1 /DCAR_030786); chalcone isomerase ( DcCHI1 /DCAR_027694) and ( DcCHIL /DCAR_019805); flavanone 3-hydroxylase ( DcF3H1 /DCAR_009483), and flavonoid 3′-hydroxylase ( DcF3’H1 /DCAR_014032); ii) cytochrome P450 (CYP450) proteins, putatively related to the flavonoid and isoflavonoid biosynthesis pathways 23,44 ; iii) ATP-binding cassette (ABC) transporters, potentially related to anthocyanin transport 45,46 ; and iv) genes from the late steps of the pathway, like dihydro-flavonol 4-reductase ( DcDFR1 /DCAR_021485), leucoanthocyanidin dioxygenase ( DcLDOX1 / DCAR_006772), and UDP-glycosyltransferase ( DcUFGT /DCAR_009823) and the recently described DcUCGXT1 /DCAR_021269 and DcSAT1 /MSTRG.8365, which were confirmed to be responsible for anthocyanins glycosylation and acylation, respectively 26,47 . Finally, most significant regulatory genes of the pathway, belonging to the MYB, bHLH and WD40 TF gene families 21,23–26 were also differentially expressed between purple and orange genotypes (Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…DcbHLH3 , DcUCGXT1 and DcSAT1 ) also displayed no tissue specificity. DcbHLH3 was described as a co-regulator in anthocyanin biosynthesis, while DcUCGXT1 and DcSAT1 participate in anthocyanin glycosylation and acylation, respectively 26,47 . Additionally, seven TFs showed xylem preferential expression-specificity, while only one was preferentially expressed specifically in phloem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The R2R3-MYB TFs were often identified as determinants of variation in anthocyanin pigmentation and have been identified in many higher plant species [12][13][14][15][16][17]. In a previous study, OsC1, OsRb and OsDFR were identified as the determinants of anthocyanin biosynthesis in rice leaves [18].…”
Section: Introductionmentioning
confidence: 99%